Structural Analysis of Modern Empires in the Framework of Global Governance Theory - Zaporozhchenko, R. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
This present paper analyzes three powerful players of the modern global governance: the United States, the Russian Federation and the People’s Republic of China. The main parameters that allow us to call them modern empires and help identify patterns of spreading influence are determined. The basic directions of geopolitical «giants» are used for comparative analysis of the imperial system of the above-mentioned countries.